Effects of a senior exercise program on functional capacity in institutionalized elderly in the municipality of Mação - Santos, Jorge (2019)
The aim of this study was to study the effects of a Senior Gymnastics Program (SGP), with duration of 12 weeks 2 times per week, on the functional capacity of the elderly in the municipality of Mação, through the application of the Senior Fitness Test (SFT). On the other hand, to perceive how Functional Capacity evolved in the elderly who did not benefit from the program. We tried to verify if an SGP, specific for this age group, caused significant effects in both genres in the improvement of the functional capacity of the institutionalized elderly. It was sought to evaluate the evolution of the functional capacity (FC) of the institutionalized elderly. who did not benefit from SGP. A quantitative, experimental, analytical and longitudinal research was carried out. The sample consisted of 2 groups of elderly institutionalized in the House of the Santa Casa da Misericórdia de Mação, one that we designated as experimental (GE) with 13 individuals (10 women and 3 men 87,15±6,09) who carried out the 12 week program and one that we denominated sedentary group (GS) with 10 (7 women and 3 men79,6 ±6,45 individuals who did not benefit from the program. As a conclusion, the experimental group showed statistically significant differences in all SFT battery tests, except for the 8 foot Up and Go again (p≥0.06).